New Magnetic Nanobiocomposite Based in Galactomannan/Glycerol and Superparamagnetic Nanoparticles - Casagrande-Denardin, J (Elsevier Ltd, 2015)
In this study, magnetic nanobiocomposites were prepared in different proportions and produced with galactomannan (GM), magnetic nanoparticles of NiZn and glycerol (GL). The microstructure and morphology of the samples were characterized by Scanning Electron Microscopy (SEM), X-ray powder diffraction, Fourier transform infrared (FTIR) spectroscopy, Thermal analysis (TG) and Differential scanning calorimetry (DSC). The magnetic and dielectric behavior of the films was studied by Vibrating sample magnetometer (VSM) and Impedance spectroscopy. The results showed efficient incorporation of NiZn in the polymer matrix. The degradation profiles presented thermal events that were confirmed by endothermic and exothermic processes from DSC measurements. Films presented saturation magnetization (Ms) range from 6 to 17 emu/g and superparamagnetic behavior. It was observed that the values of dielectric constant increased as a function of the nanoparticles concentration in the bionacomposite. Thus, this kind of biocomposite could be used as a versatile magnetic-dielectric in microwave devices. © 2015 Elsevier B.V.